Analisis Implementasi Sistem Informasi Medis Pada Fasilitas Pelayanan Kesehatan Indonesia: Literature Review terhadap Kendala dan Solusi Implementasi - Evana Anugrah Purwayanto; Dwita Urip Natasa; Deny Nugroho Triwibowo; Suryani, Riska (Jurnal IT UHB, 2025)
The adoption of digital medical record systems in Indonesia remains uneven, with approximately 60% of healthcare facilities still relying on manual processes. This study conducts a systematic literature review following PRISMA guidelines to analyze 11 peer-reviewed articles (2019-2024) on medical information system (MIS) implementation. Our analysis identifies three critical barriers: (1) infrastructure limitations (particularly in rural areas), (2) lack of trained human resources, and (3) unstable technology integration. Successful cases demonstrate that cloud-based solutions (e.g., Smart Medica Clinic) can reduce operational costs by 35%, while policy interventions like Ministry of Health Regulation No. 24/2022 strengthen legal frameworks for electronic health records. This study contributes to existing literature by focusing on Indonesia's unique socio-technical challenges and providing evidence-based recommendations for scalable digital health transformation.